2022
DOI: 10.20518/tjph.999736
|View full text |Cite
|
Sign up to set email alerts
|

The Seasonal and Demographic Trends of National HPV Screening Program in City of Niğde: The Effects of COVID 19 Pandemic

Abstract: Bütün dünyada uygulanan ulusal HPV tarama programları prekanseröz lezyonların oluşumundan önce persistan HPV enfeksiyonunun tespit edilmesini sağlayarak serviks kanserinin önlenmesinde en güvenilir, etkili ve maliyet etkinliği yüksek yöntemdir. Bu çalışmanın amacı öncelikle Niğde'de ulusal serviks kanseri tarama hedeflerinin gerçekleştirilme yüzdeleri, ilçeler bazında tarama sayıları, tarama programına katılan kadınlarda HPV sıklığı ve HPV genotiplerinin dağılımını incelemektir. İkincil olarak da Niğde ilinde … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 36 publications
0
3
0
4
Order By: Relevance
“…In our study, it was found out that 50.7% of women had cancer screening at least once in their lives, and 92.3% of women did not have cancer screening during the pandemic period. In the study of Erdoğan and Akkaya [ 23 ], it was found out that due to COVID-19 pandemic, HPV scanning decreased significantly in 2020 compared to previous years. The studies conducted by Peacock et al [ 24 ] in Belgium, by Jacob et al [ 25 ] in Germany and by Skovlund et al [ 26 ] in Denmark all shown that cancer diagnosis in the pandemic has decreased significantly compared to the pre-pandemic period.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, it was found out that 50.7% of women had cancer screening at least once in their lives, and 92.3% of women did not have cancer screening during the pandemic period. In the study of Erdoğan and Akkaya [ 23 ], it was found out that due to COVID-19 pandemic, HPV scanning decreased significantly in 2020 compared to previous years. The studies conducted by Peacock et al [ 24 ] in Belgium, by Jacob et al [ 25 ] in Germany and by Skovlund et al [ 26 ] in Denmark all shown that cancer diagnosis in the pandemic has decreased significantly compared to the pre-pandemic period.…”
Section: Discussionmentioning
confidence: 99%
“…Ülkemizde, ulusal serviks kanseri tarama programı Sağlık Bakanlığı Kanser Dairesi Başkanlığı tarafından 2014 yılından itibaren yürütülmektedir. Bu program çerçevesinde 30-65 yaş arası kadınlar 5 yıl aralıklarla Kanser Randevu Sistemi ya da telefon aracılığıyla sağlık kuruluşlarına davet edilmekte ve rahim ağzı sürüntüsü alınarak HPV DNA testi yapılmaktadır [35,36]. Kişinin geçmiş tarama sonuçları Aile Hekimliği Bilgi Sistemi üzerinden kontrol edilerek kişiye uygun zaman için randevu verilmektedir [36].…”
Section: Korunma Yöntemleriunclassified
“…Kişinin geçmiş tarama sonuçları Aile Hekimliği Bilgi Sistemi üzerinden kontrol edilerek kişiye uygun zaman için randevu verilmektedir [36]. Ulusal tarama programında HPV tipleri 16,18,31,33,35,39,45,51,52,56,58,59 ve 68 bakılmaktadır. Riskli grup HPV tespit edilen kadınların rahim ağzı sürüntülerinden Pap Smear alınıp sitolojik inceleme yapılmaktadır.…”
Section: Korunma Yöntemleriunclassified
See 2 more Smart Citations